Controversies in Implementing English as a Second Language Policy in Papua: Perspectives of English Teachers - Dabamona, Miftahulfadlik; Suharmoko; Hidayat, Arrofi; Gay, Aprilia; Ayuningsih, Baiq Septia (The Indonesian Institute of Science and Technology Research, 2025)
Language Policy of English as a Second Language (ESL) in Papua has been established by the Special Autonomy Law in 2021. This is pivotal in educational practices in a multilingual context. Despite this, significant concerns remain, especially about teachers’ involvement and the execution of the regulation. The gap policy arises from the previous studies highlighting the policy intention and classroom practices. This study aims to explore the gaps in the policy due to three main themes, namely communication gaps, structural and professional support, and socio-cultural tensions and language ideologies. A qualitative study was conducted by applying in-depth interviews with 6 teachers from several regencies in West Papua and Southwest Papua Province. Thematic analysis exposed three main challenges: (1) policy communication gaps; (2) limited structural and professional support; (3) socio-cultural tensions and language ideologies. This study shows that the success of ESL policy depends on the provincial government's engagement, sustained teacher training, and culturally sensitive curriculum to local wisdom. Ultimately, this research contributes to the discourse of language policy in multilingual contexts, emphasizing the respect for local values and adjusting to the multilingual context, like Papua.